Technical note: The calculated real world BNT162b2 vaccine efficacy was 88% when accounting for asymptomatic cases - Richard Paul Junghans (Taylor & Francis Group, 2021)
COVID-19 trials have relied on symptomatic subjects for judging the effectiveness of vaccine candidates, whereas asy-mptomatic subjects have been suspected as the main driver of the pandemic. An assumption of the same impact on symptomatic and asymptomatic breakthrough infections is shown to be flawed, resulting in an overestimate of the vaccines' true effectiveness. Recent available data provide the first large-scale unbiased data on asymptomatic versus symptomatic infections postvaccination, providing a unique opportunity to reassess the true infection rates after vaccination. By this, the breakthrough of the BNT162b2 vaccine is seen to be 12% rather than 5% for a corrected overall efficiency (symptomatic + asymptomatic) of 88% with the original virus strain in a real-world setting.